MEMBERS OF SOME DIAGNOSTIC SMALL CALCAREOUS LAGENID BENTHIC FORAMINIFERAL GENERA LINGULINA, TRISTIX AND CITHARINA - Haidar Salim Anan (Geological Behavior, 2022)
This study deals with the taxonomy, stratigraphy, and paleogeography of ten Campanian-Paleogene diagnostic calcareous benthic foraminiferal species belong to three lagenid genera which were erected from many localities in the world (North America, Europe and North Africa). These taxa are: Lingulina (L. carinata, L. sliteri), Tristix (T. liasina, T. aubertae, T. sliteri, T. sztrakosae), Citharina (C. strigillata, C. polonica, C. plummerae, C. plumoides). Four of these species, were recorded from three different localities in the world (Mexico, Poland, France, Egypt) are believed to be new: (1) The Late Campanian Lingulina sliteri Anan, n. sp. from Mexico, (2) The Early Maastrichtian Tristix sliteri Anan, n. sp. from Mexico, (3) The Lutetian Tristix sztrakosae Anan, n. sp. from France, and (4) The Danian Citharina polonica Anan, n. sp. from Poland. These taxa show an affinity with Midway-Type Fauna (MTF). The paleogeographic distribution of the recorded species indicate an open connection between the Atlantic and Indo-Pacific Oceans in that time.